A microRNA Signature for Impaired Wound-Healing and Ectopic Bone Formation in Humans. (4th November 2020) - de Vasconcellos, Jaira F.; Jackson, Wesley M.; Dimtchev, Alexander; Nesti, Leon J.
Abstract : Background: Heterotopic ossification (HO) is characterized by the abnormal growth of ectopic bone in soft tissues, frequently occurring within the military population because of extensive orthopaedic combat trauma. MicroRNAs (miRNAs) are small noncoding RNAs that act as post-transcriptional regulators of gene expression. We hypothesized that a clinically relevant miRNA signature could be detected in patients following injury that progressed to form HO (HO+) or did not form HO (HO−). Methods: Tissue samples were obtained from injured servicemembers during their initial surgical debridements, and miRNA profiling was performed using a real-time miRNA polymerase chain reaction (PCR) array. Primary mesenchymal progenitor cells (MPCs) were harvested from debrided traumatized human muscle tissue, and cells were isolated and cultured in vitro. Mimic miRNAs were transfected into MPCs, followed by downstream in vitro analyses. Results: The investigation of the miRNA expression profile in the tissue of HO+ compared with HO− patients demonstrated a molecular signature that included the upregulation of miR-1, miR-133a, miR-133b, miR-206, miR-26a, and miR-125b. Transfection of each of these mature miRNAs into MPCs followed by osteogenic induction demonstrated that miR-1, miR-133a, miR-133b, and miR-206 enhanced osteogenic differentiation compared with control treatments. In silico and in vitro analyses identified the transcription factor SOX9 as a candidate downstream target of miR-1 and miR-206 miRNAs. Conclusions: Our data demonstrated a molecular signature of miRNAs in the soft tissue of wounded servicemembers that was associated with the development of HO, providing novel insights into the underlying molecular mechanisms associated with posttraumatic HO. Level of Evidence: Prognostic Level II . See Instructions for Authors for a complete description of levels of evidence.